Outpatient tubeless percutaneous nephrolithotomy and concomitant cystolitholapaxy - Lehmann, Kyle J; Beiko, Darren (Canadian Urological Association Journal, 2014)
Percutaneous nephrolithotomy (PCNL) is a widely employed endourologic procedure to remove renal stones. Traditionally, PCNL has been performed on an inpatient basis, with patients routinely hospitalized postoperatively. Given the ongoing rising healthcare costs, a shift toward outpatient surgery is desirable. We report the case of a 21-year-old female who was safely discharged a few hours following uncomplicated tubeless PCNL and concomitant cystolitholapaxy for a stent with encrustation on its distal coil. To the best of our knowledge, this is the first published case of tubeless PCNL with concomitant cystolitholapaxy performed on an entirely outpatient basis.